Parental satisfaction with early intensive behavioral intervention. (September 2019) - Grey, Ian; Coughlan, Barry; Lydon, Helena; Healy, Olive; Thomas, Justin
Research related to parental satisfaction with early intensive behavioral intervention (EIBI) remains limited. A 35-item questionnaire called the parental satisfaction scale–EIBI (PSS-EIBI) was developed with four subdomains (child outcomes, family outcomes, quality of the model, and relationship with the team). Study 1 assessed levels of satisfaction for 48 parents with their child's EIBI program after approximately 1 year of intervention. Study 2 examined the relationship between parental satisfaction, length of child participation in EIBI, and the relationship between parental satisfaction and actual outcomes for their child as assessed by the Verbal Behavior Milestones Assessment and Placement Program after approximately 2 years. Results indicate that parental satisfaction with EIBI was consistently high in all four domains of the PSS-EIBI in both studies. Parental satisfaction was found to be associated with gains in child functioning after 1 year of intervention.